Active oxygen acts as a promoter of transformation in mouse embryo C3H/10T1/2/C18 fibroblasts. - Zimmerman, R (1984)
There is much evidence from in vivo and in vitro carcinogenesis studies that active oxygen species play a role in tumor promotion. We tested directly whether superoxide produced extracellularly by xanthine-xanthine oxidase (X-XO) has the capacity to promote initiated mouse embryo C3H/10T1/2 fibroblasts. Cell cultures initiated with either 137Cs gamma-rays or benzo[a]pyrene diol epoxide I were found to transform 3-30 times more effectively when subsequently treated daily for 3 weeks with nontoxic doses of X-XO. Scavengers of active oxygen radicals such as superoxide dismutase or superoxide dismutase in combination with catalase reduced the frequency of appearance of transformed foci by 3-25 times when compared to cultures receiving X-XO alone. These results show that active oxygen species such as superoxide and H2O2 can act in a promotional manner that mimics the effects of the mouse skin promoter phorbol 12-myristate 13-acetate in this system. X-XO also acted as a weak complete carcinogen.